2001
DOI: 10.1111/1467-9507.00170
|View full text |Cite
|
Sign up to set email alerts
|

Attention to Language: Lessons Learned at the Dinner Table

Abstract: The ordinary discourse of parents, and to a lesser degree young children, includes a surprising amount of attention to language. The dinner table conversations of 22 middle class families, each with a child between 2 and 5 1 / 2 years of age, were recorded. Transcripts of these conversations were analyzed for the presence and function of language-focused terms, words such as say, ask, tell, and speak. More than 11% of mothers', 7% of fathers', and 4% of children's utterances contained a languagefocused term. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 43 publications
1
21
0
1
Order By: Relevance
“…More than a third of fathers' and a little more than 10% of mothers' talk during reading was metalingual, suggesting that many low-income children are engaged in high-quality reading, especially from their fathers. These findings are generally consistent with past studies that highlight variability among low-income families and extend the literature by showing that low-income fathers, as it has been found with middle-class fathers, also use high levels of metalingual talk with their children (Ely et al, 2001). We also found that metalingual talk by both parents is indirectly related to pre-kindergarteners' receptive vocabulary through children's interest in reading.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More than a third of fathers' and a little more than 10% of mothers' talk during reading was metalingual, suggesting that many low-income children are engaged in high-quality reading, especially from their fathers. These findings are generally consistent with past studies that highlight variability among low-income families and extend the literature by showing that low-income fathers, as it has been found with middle-class fathers, also use high levels of metalingual talk with their children (Ely et al, 2001). We also found that metalingual talk by both parents is indirectly related to pre-kindergarteners' receptive vocabulary through children's interest in reading.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, among middle-class families, fathers have been found to use more metalingual talk (e.g. labeling) than mothers during linguistic interactions with their children (Ely, Gleason, MacGibbon, & Zaretsky, 2001). We know of no research that examines the nature and frequency of metalingual talk among low-income fathers.…”
Section: Introductionmentioning
confidence: 99%
“…Metalinguistic awareness has been primarily explored as a facet of language development in young monolingual children, some of who are speakers of non-standard dialects (Aukrust, 2004;Becker, 1988;Blum-Kulka, 1997;Clark, 2014;Connor & Craig, 2006;Ely, Gleason, MacGibbon & Zaretsky, 2001;Stude, 2007); as a contributor to literacy development via its impact on morphological, phonological, syntactic and vocabulary awareness for monolingual, developing readers (Downing & Valtin, 1984;Lundberg, Frost & Petersen, 1988;Nagy, 2007;Terry & Scarborough, 2011;Terry, 2014;Tong, Deacon & Cain, 2014); and as an essential component of bi-and multi-lingual proficiency (Bialystok & Craik, 2010;Swain, 1998Swain, , 2000. In contrast, we focus here on predominately monolingual middle graders' metalinguistic awareness of academic registers.…”
Section: Metalinguistic Register Awarenessmentioning
confidence: 99%
“…More recently, Connor and Craig (2006) suggest that African American preschoolers are developing bidialectal capacities as evidenced by their use of fewer features of African American English (AAE) in more formal speech settings with non-kin interlocutors. Still other studies provided evidence that children reflect and comment explicitly from an early age on language and its use (Aukrust, 2004;Becker, 1988;Blum-Kulka, 1997;Ely, Gleason, MacGibbon & Zaretsky, 2001;Stude, 2007).…”
Section: Metalinguistic Register Awarenessmentioning
confidence: 99%
“…Bilmes et al 2015). Defining words represents a 'metalinguistic awareness', or the ability to reflect on and talk about language (e. g. Silverstein 1981), and is an explicit means of informal instruction at the dinner table (e. g. Ely et al 2001). Definitions minimally involve the introduction of a lexical item followed by an explication of its meaning, and they can be either proffered or requested from another.…”
Section: Defining Words and Relating Their Cultural Connectionsmentioning
confidence: 99%